2017
DOI: 10.1155/2017/4896036
|View full text |Cite
|
Sign up to set email alerts
|

Combined Phacoemulsification and Intravitreal Dexamethasone Implant (Ozurdex®) in Diabetic Patients with Coexisting Cataract and Diabetic Macular Edema

Abstract: Purpose To investigate the effectiveness and safety of combined phacoemulsification and dexamethasone intravitreal implant in patients with cataract and diabetic macular edema. Methods In this two-center, retrospective, single-group study, the charts of 16 consecutive patients who underwent combined phacoemulsification and intravitreal dexamethasone implant were retrospectively reviewed. These 16 patients, 7 men and 9 women, were observed at least 3 months of follow-up. Primary outcome was the change of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 31 publications
4
42
0
2
Order By: Relevance
“…Regarding the optimal time of intravitreal dexamethasone implant insertion in patients with DME and cataract, there are various approaches. Previous studies have used dexamethasone implant either at the beginning or immediately after surgery in an attempt to prevent or control postoperative macular edema [27][28][29][30][31]35 . Agarwal et al used intravitreal dexamethasone implant in 18 eyes with DME and cataract, at the beginning of phacoemulsification, reporting 15-18 letters gain in visual acuity compared to stable visual acuity in controls associated with a decrease in CMT 35 , while Sze et al also showed improvement in BCVA and CST using dexamethasone implant just before initiation of cataract surgery, but about 10% of patients required further treatment due to recurrence of macular edema in about 21 weeks post-operation 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the optimal time of intravitreal dexamethasone implant insertion in patients with DME and cataract, there are various approaches. Previous studies have used dexamethasone implant either at the beginning or immediately after surgery in an attempt to prevent or control postoperative macular edema [27][28][29][30][31]35 . Agarwal et al used intravitreal dexamethasone implant in 18 eyes with DME and cataract, at the beginning of phacoemulsification, reporting 15-18 letters gain in visual acuity compared to stable visual acuity in controls associated with a decrease in CMT 35 , while Sze et al also showed improvement in BCVA and CST using dexamethasone implant just before initiation of cataract surgery, but about 10% of patients required further treatment due to recurrence of macular edema in about 21 weeks post-operation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al used intravitreal dexamethasone implant in 18 eyes with DME and cataract, at the beginning of phacoemulsification, reporting 15-18 letters gain in visual acuity compared to stable visual acuity in controls associated with a decrease in CMT 35 , while Sze et al also showed improvement in BCVA and CST using dexamethasone implant just before initiation of cataract surgery, but about 10% of patients required further treatment due to recurrence of macular edema in about 21 weeks post-operation 28 . Other authors preferred to insert the intravitreal dexamethasone implant at the end of the surgery, when potential intraoperative complications were overcome and a better visualization of the implant in the vitreous was possible, also demonstrated good anatomical and functional outcomes 27,[29][30][31] . In our study, however, about 35% of patients presented recurrent macular edema 3 months postoperatively, suggesting that re-insertion of dexamethasone implant may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently dexamethasone slow release implant (Ozurdex 0.7 mg) has been used in various studies in refractory diabetic macular edema and has shown promising results. [16][17][18] The availability of this implant is a major limitation for its use in our setup.…”
Section: Discussionmentioning
confidence: 99%
“…DME je najčešći uzročnik gubitka vida kod pacijenata s dijabetičkom retinopatijom i zahvaća oko 25 % pacijenata s dijabetičkom retinopatijom (DR, engl. diabetic retinopathy) 11 . Kod DME-a, osim disfunkcije hematookularne barijere i kronične subkliničke upale, ulogu ima oksidativni stres uzrokovan hiperglikemijom, gubitak pericita, hipoksija, depoziti završnih produkata uznapredovale glikacije (AGE, engl.…”
Section: Dijabetički Makularni Edemunclassified
“…Munk i sur. opisali su OCT promjene po kojima se može 11 . "Prevention of macular edema after cataract surgery" je studija čiji je cilj uspostaviti algoritam liječenja baziran na dokazima postoperativnog CME-a kod pacijenata sa ili bez šećerne bolesti.…”
Section: Razlike Između Cistoidnog Makularnog Edema I Dijabetičkog Edemaunclassified